The Disappearing Girl Child! It is P The Disappearing Girl Child! It is Possible to Save Her!! ossible to Save Her!! - Devendra, Kiran; Kumar, Krishan (THE PRIMARY TEACHER, 2008)
The focus of this paper is on an urgent need to save the girl child, take care of her health emotional and educational needs and her self-esteem to ensure an empowered woman of our country. It discusses the crime against the girl child in a secure place, her mother’s womb, (female foeticide) if she is allowed to be born, her own parents kill her (female infanticide) if she escapes these, she faces intentional neglect in her own family and later in her husband’s. With the Government making every possible effort to save the girl child, the situation continues to be grim and sad for the girl child in India. However, the paper discusses how a sensitive and a strong administration could successfully save the girl child in a district of Punjab with continuous efforts. The district Nawanshahar was able to save the female foetuses and raised the sex ratio in 2006.